Elevated Serum Gamma‐Glutamyl Transferase as a Risk Factor for Frailty in Older Men: A Nationwide Population‐Based Study - Kang, Min‐gu; Jung, Hee‐Won; Kim, Beom‐Jun (Journal of cachexia, sarcopenia and muscle, 2025)
ABSTRACT Background Oxidative stress is a key driver of accelerated ageing, and gamma‐glutamyl transferase (GGT), an essential enzyme involved in the metabolism of glutathione, a major antioxidant, plays a pivotal role in the generation of free radical species. This study aimed to explore the potential utility of circulating GGT as a biomarker of frailty, which reflects biological ageing and overall health status. Methods This cross‐sectional, population‐based study included 2526 community‐dwelling adults aged 65 years and older, using data from the Korea National Health and Nutrition Examination Survey. Frailty was assessed using a deficit accumulation frailty index (FI) derived from 36 items encompassing physical, cognitive, psychological, and social domains. Participants were categorised as nonfrail (FI ≤ 0.15), prefrail (0.15 < FI ≤ 0.25), or frail (FI > 0.25). Serum GGT levels were determined using an enzymatic activity assay. Results After adjusting for potential confounders including age, body mass index, socioeconomic status, lifestyle factors, and medical history, serum GGT levels were 26.0% higher in frail men than in nonfrail men (p = 0.010). Amongst men, serum GGT concentrations were positively correlated with the FI (p = 0.001), and each standard deviation increase in serum GGT was associated with a 1.36‐fold higher odds of frailty (p = 0.001). Additionally, older men in the highest GGT quartile exhibited a significantly higher FI and a 2.08‐fold increased odds of frailty compared to those in the lowest quartile (p = 0.010 and p = 0.019, respectively). In women, however, no significant association was observed between serum GGT levels and frailty. Conclusion Elevated serum GGT levels were significantly associated with frailty in older men, suggesting their potential as a biomarker of biological ageing. Nonetheless, the cross‐sectional design precludes causal inference, and longitudinal studies are warranted to explore whether elevated GGT contributes to the onset or progression of frailty over time.